'Florida Elyana' Strawberry - Craig K. Chandler; Bielinski M. Santos; Natalia A. Peres (EDIS)
HS-1150, a 2-page illustrated fact sheet by C.K. Chandler, B.M. Santos, and N.A. Peres, describes the performance of this short-cultivar that has shown promise in recent trials in western portions of Central Florida. Includes references. Published by the UF Department of Horticultural Sciences, December 2008.